Thermal Stability of siRNA Modulates Aptamer- conjugated siRNA Inhibition - Alexey Berezhnoy; Randall Brenneman; Marcio Bajgelman; Dawn Seales; Eli Gilboa (Elsevier, 2012)
Oligonucleotide aptamer-mediated in vivo cell targeting of small interfering RNAs (siRNAs) is emerging as a useful approach to enhance the efficacy and reduce the adverse effects resulting from siRNA-mediated genetic interference. A current main impediment in aptamer-mediated siRNA targeting is that the activity of the siRNA is often compromised when conjugated to an aptamer, often requiring labor intensive and time consuming design and testing of multiple configurations to identify a conjugate in which the siRNA activity has not been significantly reduced. Here, we show that the thermal stability of the siRNA is an important parameter of siRNA activity in its conjugated form, and that siRNAs with lower melting temperature (Tm) are not or are minimally affected when conjugated to the 3' end of 2'F-pyrimidine-modified aptamers. In addition, the configuration of the aptamer-siRNA conjugate retains activity comparable with the free siRNA duplex when the passenger strand is co-transcribed with the aptamer and 3' overhangs on the passenger strand are removed. The approach described in this paper significantly reduces the time and effort necessary to screening siRNA sequences that retain biological activity upon aptamer conjugation, facilitating the process of identifying candidate aptamer-siRNA conjugates suitable for in vivo testing.